2008
DOI: 10.1080/09540120701693966
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of and responses to HIV among African and Caribbean communities in Toronto, Canada

Abstract: African and Caribbean communities in Canada and other developed countries are disproportionately affected by HIV/AIDS. This qualitative study of African and Caribbean communities in Toronto sought to understand HIV-related stigma, discrimination, denial and fear, and the effects of multiple intersecting factors that influence responses to the disease, prevention practices and access to treatment and support services. Semi-structured interviews were conducted with 30 HIV-positive men and women and focus groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 15 publications
5
42
0
Order By: Relevance
“…Although the provision of 'ethno-specific' services in this country indicates significant progress over earlier colour-blind approaches to HIV and AIDS (Catungal 2013), race has had a clear bearing on various aspects of health (prevention, access to services and health outcomes), and at different levels (structural, social and personal) of individual experience. In their study of the experiences of, and responses to, HIV among African and Caribbean communities in Toronto, Gardezi et al (2008) found that men and women in these communities face a wide range of interconnected issuespoverty, racism, unemployment, housing, social isolation and traditional norms around sexuality -that may increase their risk of HIV infection, create obstacles to testing and treatment and lead to the isolation of HIV-infected people. For young people from these communities, their fear of encountering racism and distrust in the health system also inhibits them from accessing sexual health services (Salehi, Hynie, and Flicker 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the provision of 'ethno-specific' services in this country indicates significant progress over earlier colour-blind approaches to HIV and AIDS (Catungal 2013), race has had a clear bearing on various aspects of health (prevention, access to services and health outcomes), and at different levels (structural, social and personal) of individual experience. In their study of the experiences of, and responses to, HIV among African and Caribbean communities in Toronto, Gardezi et al (2008) found that men and women in these communities face a wide range of interconnected issuespoverty, racism, unemployment, housing, social isolation and traditional norms around sexuality -that may increase their risk of HIV infection, create obstacles to testing and treatment and lead to the isolation of HIV-infected people. For young people from these communities, their fear of encountering racism and distrust in the health system also inhibits them from accessing sexual health services (Salehi, Hynie, and Flicker 2014).…”
Section: Introductionmentioning
confidence: 99%
“…16 These interacting stigmas may directly impede HIV-reduction efforts. As noted by Gardezi et al (2008), black PHA accessing medical care report cultural insensitivity among service providers (i.e., negative remarks about one's ethnic/racial group, discourteous service) thus undermining quality of healthcare among this group. 17 These barriers can undermine effective HIVreduction approaches in African American communities.…”
mentioning
confidence: 99%
“…In our population, although ethnic minority men had similar HIV testing rates as white men, the ethnic minority women reported significantly lower testing rates than white women. Gardezi and coworkers found that ethnic minority women in Toronto did not consider themselves at risk partly because of their religious beliefs and cultural norms [24]. Although we did not have information on perception of risk, HIV testing was lowest in ethnic minority women.…”
Section: Discussionmentioning
confidence: 83%